Why Optum Insight could help UnitedHealth Group win the AI war. - Tong, Noah (Modern Healthcare, 2026)
The article focuses on UnitedHealth Group's leadership in integrating artificial intelligence (AI) within the healthcare sector, particularly through its Optum Insight division, which provides data analytics and consulting services to other healthcare companies. UnitedHealth Group is investing heavily in AI, with $1.5 billion allocated this year, and markets various AI-driven tools such as Optum Real for prior authorization and Optum Value Connect for value-based care, serving thousands of providers and health plans. Optum Insight’s external commercialization of AI products distinguishes UnitedHealth Group from competitors, potentially offering a competitive advantage in the healthcare AI market. Other companies like Elevance Health, CVS Health, Clover Health, and Highmark Health also use AI but on a smaller scale or with less external focus.